SOME PROBLEMATIC ASPECTS OF FLOOD ROUTING CALCULATIONS - Gopchenko Y.D. (My University, 1988)
Among the formulas widely used in rainfall-induced flood routing calculations for water-conservancy forecasting purposes are the so-called 'peak, or maximum intensity of flood' formulas. We note that fundamental changes have been made in the structure of these formulas in recent years. Soviet hydrologists have further developed for maximum-intensity formula both by refining the values of the parameters and developing a theoretical basis for the formula itself. Unfortunately, less attention has been devoted to evaluating the degree of optimality of the original model on which the theoretical derivations have been based, which ultimately has given rise to certain assumptions that more or less contradict the principle of 'maximum intensity.'